Draft Genome of Proteus mirabilis Serogroup O18 Elaborating Phosphocholine-Decorated O Antigen - Czerwonka, Grzegorz; Gmiter, Dawid; Durlik-Popińska, Katarzyna (Frontiers in Cellular and Infection Microbiology, 2021)
Proteus mirabilis is a pathogenic, Gram-negative, rod-shaped bacterium that causes ascending urinary tract infections. Swarming motility, urease production, biofilm formation, and the properties of its lipopolysaccharide (LPS) are all factors that contribute to the virulence of this bacterium. Uniquely, members of the O18 serogroup elaborate LPS molecules capped with O antigen polymers built of pentasaccharide repeats; these repeats are modified with a phosphocholine (ChoP) moiety attached to the proximal sugar of each O unit. Decoration of the LPS with ChoP is an important surface modification of many pathogenic and commensal bacteria. The presence of ChoP on the bacterial envelope is correlated with pathogenicity, as decoration with ChoP plays a role in bacterial adhesion to mucosal surfaces, resistance to antimicrobial peptides and sensitivity to complement-mediated killing in several species. The genome of P. mirabilis O18 is 3.98 Mb in size, containing 3,762 protein-coding sequences and an overall GC content of 38.7%. Annotation performed using the RAST Annotation Server revealed genes associated with choline phosphorylation, uptake and transfer. Moreover, amino acid sequence alignment of the translated licC gene revealed it to be homologous to LicC from Streptococcus pneumoniae encoding CTP:phosphocholine cytidylyltransferase. Recognized homologs are located in the O antigen gene clusters of Proteus species, near the wzx gene encoding the O antigen flippase, which translocates lipid-linked O units across the inner membrane. This study reveals the genes potentially engaged in LPS decoration with ChoP in P. mirabilis O18.